Programa de aquisição de alimentos com doação simultânea: um estudo de caso no município de Mossoró-RN - Medeiros, Cleiton Dantas de (Universidade Federal Rural do Semi-Árido, 2017)
The Program for the Acquisition of Foods with Simultaneous Donation represents for family agriculture the organization of production and the certainty of marketing with fair prices. Products purchased from family agriculture are donated to people in food and nutritional insecurity, promoting the human right to adequate food, especially to school children and the elderly. In Mossoró-RN, the program has been in operation since 2006, being implemented by the Rio Grande do Norte Technical Assistance and Rural Extension Institute - EMATER-RN, benefiting several family farmers and institutions. In this sense, the present study sought to analyze the management and execution of the PAA with Simultaneous Donation, in the period from 2014 to 2017, in the municipality of Mossoró-RN. Throughout the study, some of the main obstacles in the management and execution of the program in Mossoró were identified, involving bureaucratic, logistical and climatic issues, such as: discontinuity of the program in recent years; prolonged drought, which has hindered agricultural and livestock production in the municipality and region; insufficient and precarious logistical support provided by the City Hall; and difficulty in accessing the Declaration of Aptitude to PRONAF by the farmers of Settlement Projects
Monografia
Keywords: EMATER-RN; Agricultura Familiar; PAA; Comercialização; EMATER-RN; Family farming; PAA; Commercialization; CIENCIAS AGRARIAS::AGRONOMIA